La forme scolaire déniée des médiations muséales. Enquête sur l’accompagnement des publics - Samuel Coavoux; Frédérique Giraud (Cahiers de la Recherche sur l'Education et les Savoirs)
Is school a positive or a negative model for museums? This article analyses museum education programs oriented towards children in three museums, two traditional and one on-line museum of children art. Drawing on interviews and observations, it shows that the school model is presented as a deterrent in art professionals’ discourses. Art education projects are conceived against traditional school education. However, it appears that, in their actual work, art educators rely on scholar resources and on the scholar dispositions of their audience. We shed light on a chain of misunderstandings regarding school, between the intentions of art educators and their audience.